HUBUNGAN LITERASI FINANSIAL (BERSARANA BANK SAMPAH) DENGAN KREATIVITAS EKONOMI SISWA KELAS XI PROGRAM KEAHLIAN AKUNTANSI DAN KEUANGAN LEMBAGA SMK NEGERI 6 PEKANBARU - Septi Suarmita; Gimin Gimin; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to find out the relationship betweeen financial literacy of waste banks with the creativity of class XI Accounting and Financial Institution Expertise Programs at Pekanbaru State Vocational High School 6. This research was conducted from December to March 2019. The population in this study were students of class XI of the Accounting Expertise Program and Financial Institutions of Pekanbaru State Vocational High School which consist of 124 students. There were 95 respondents in this study that was chosen by Proportional Sampling techniques. Data collection techniques were carried out through questionnaires. Then the data were analyzed using (a) descriptive analysis, (b) Spearman Correlation analysis. Description analysis was counted by making a percentage calculation with the results of 49.47% (47 respondents) have high category of economic creativity and 64.21% (61 respondents) have low financial literacy category. While the Spearman Correlation analysis was obtained with a displacement coefficient of 0.397. It means that the level of strength of the relationship (interaction) between Financial Literacy Literacy variables with Waste Bank and Economic Creativity of 0.397 or related are not strong. It can be concluded that there is a low positive relationship between financial literacy with waste bank and the creativity of students of class XI Accounting Expertise Program and Financial Institution of SMK Negeri 6 Pekanbaru. It is expected that schools will stimulate waste bank activities as a means of creativity in the economic field to increase financial literacy.Key Words: Financial Literacy, Economic Creativity.